What did GLOBE really measure? Researchers’ minds versus respondents’ minds - Hofstede, Geert (Journal of International Business Studies, 2006)
The GLOBE research program expanded the Hofstede model of five dimensions of national cultures to 18. A re-analysis based on GLOBE's 2004 summary book produced five meta-factors. One was significantly correlated with GNP/capita and, from the Hofstede dimensions, primarily with Power Distance. Three more correlated significantly with Hofstede's Individualism, Uncertainty Avoidance and Long-Term Orientation. The fifth included the few GLOBE questions that related to Hofstede's dimension of Masculinity versus Femininity. GLOBE's respondents’ minds classified the questions in a way that the researchers’ minds did not account for and which closely resembles the original Hofstede model.